KAJIAN KOMUNIKASI BUDAYA MELAYU PADA CHANNEL YOUTUBE APRESIASI DARI KEPRI - Sitorus, Ronalisa; Rorong , Michael Jibrael (LPPM Universitas Putera Batam, 2024)
Malay culture is a culture that has been passed down from generation to generation and is carried out by the community. It cannot be denied that the Malay civilization is one of the foundations of civilization in Southeast Asia, such as Indonesia, Malaysia, Cambodia, the Philippines, Sri Lanka, up to Madagascar and South Africa, which are countries that are members of Southeast Asia. One of the regions in Indonesia that adheres to Malay culture is the Riau Islands province, where this culture is described by one of the Youtube channel accounts, Apresiasi Dari Riau Islands. This channel depicts Malay culture packaged in the form of video content. The aim of this research is to find out the patterns and forms of communication found on the Apresiasi Dari Kepri channel, as well as to see how Malay culture is displayed on this channel. The data collection technique in this research is a data collection technique using netnography which can be done via the internet to communicate with participants. The method used is netnography and a qualitative approach. The results of this research are that there are two communication patterns found on the Appreciation From Kepri YouTube channel, namely a linear communication pattern and a reciprocal or two-way communication pattern. The form of communication found on this channel is a form of mass communication, and this channel depicts Malay culture based on habits that actually occur in Malay society in a certain area.